PREDIKSI HARGA LOGAM MULIA DENGAN PENDEKATAN ALGORITHMA NAÏVE BAYES DAN PSO - Sri Indriyani; Muhamad Fatchan; Andri Firmansyah (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Gold is a yellow precious metal that is malleable and can be formed with high value. Gold is an exchange rate that was used in ancient times before money existed as it is today. Gold can also be used as a gold investment which can be profitable and has little risk. Currently, gold is divided into two types, namely gold for jewelry and gold for investment. Investing in gold is investing in gold stocks or gold futures. Naive Bayes Algorithm The Bayesian classifier is a statistical classifier and is based on Bayes' theorem. From the test results, the sample data presented were 120 data, then the results of the gold data stated the level of accuracy, recall and precision naïve Bayes, the accuracy rate was 84.17%, Recall was 84.21% and Percision was 82.76%.